Struggle for Seeking Knowledge in A Foreign Country in Ahmed Shawqi's Syuhadā’ul-`Ilmi wal-Gharbah: A Semiotic Analysis - Eva Farhah (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2020)
This research aims to reveal the semiotic meaning contained in the poem entitled Syuhadā’ul-`Ilmi wal-Gharbah written by Ahmed Shawqi. Shawqi saw and observed the conditions of the Egyptian people at that time who were experiencing difficulties, sorrow, poverty, ignorance, and British colonialism. Therefore, the Egyptian government sent young people to western countries to study in the hope that after returning to Egypt, they could build their country and nation. In order to reveal the semiotic meaning contained in the poem entitled Syuhadā’ul-`Ilmi wal-Gharbah, the semiotic theory was used through methods of heuristic reading and hermeneutic reading or retroactive reading. Meanwhile, the reading technique was conducted by reading one by one or reading gradually from the heuristic reading to the hermeneutic reading or retroactive reading. The results of the research indicated that knowledge was one of the ways to solve the problems of poverty, ignorance, and resistance to British colonialism in Egypt. However, in reality, young Egyptians who were sent to western countries had accidents and killed them. Therefore, Shawqi emphasized that Egyptian youths remained patient and enthusiastic about seeking knowledge in a foreign country in order to build their state and nation in the future.